Pengaruh Literasi Keuangan, Self Control dan Inklusi Keuangan Terhadap Perilaku Menabung (Survei Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Perjuangan Tasikmalaya) - Rima Nuraeni; Rita Tri Yusnita; Nita Fauziah Oktaviani (Universitas Dehasen Bengkulu, 2024)
The aim of this research is to understand the influence of financial literacy, self-control and financial inclusion on saving behavior (survey of students at the Faculty of Economics and Business, Universitas Perjuangan Tasikmalaya). This research uses a quantitative causality method with a survey approach. The population taken in this research were students from the Faculty of Economics and Business, Universitas Perjuangan Tasikmalaya who were still active in 2023-2024. With a research sample of 100 respondents. The technique for determining the sample in this research uses nonprobability sampling, precisely using incidental sampling techniques. The data obtained in this research are primary data and secondary data. The analytical tool used in this research is multiple regression using SPSS Version 25. Based on the results of the F test, it shows that financial literacy, self-control and financial inclusion simultaneously have a significant effect on saving behavior. Based on the results of the T test, it shows that financial literacy and self-control partially have a significant effect on saving behavior. Meanwhile, partial financial inclusion has no significant effect on saving behavior.